A new semi-empirical damage tolerance and fatigue evaluation approach for composite rotorcraft airframe structures - Engleder, A.; Francescatti, D.; Arelt, R.; Burger, U. (My University, 2015)
A new semi-empirical methodology to perform a damage tolerance and fatigue evaluation for composite airframe Principal Structural Elements (PSE) is proposed, to comply to new CS/FAR requirement §29.573. "Damage tolerance and fatigue evaluation of composite rotorcraft structures". This methodology consists out of five different steps. 1st , identification of airframe PSE based on the consequence of their failure, e.g. by a FMECA. 2nd , individual threat assessment for each PSE, based on in-service experience, in-house and from others. 3rd, determination of detectability thresholds for individual PSE by performing impact tests on specific coupons to derive Barely Visible Impact Damages (BVID)/ Clearly Visible Impact Damage (CVID) detectability thresholds and CVID/Obvious damage detectability thresholds. 4th, no-growth demonstration of damages on impacted coupons by applying repeated loads with constant amplitude for a certain number of load cycles which cover one design service goal (DSG/life). Those test results are then used to derive allowables in terms of strain limits for sizing of PSE. 5th, structural full scale component tests (static and fatigue) of PSE with BVID/CVID and other typical in-service damages and repairs, to verify Design Ultimate Load (DUL) capability, no-growth behavior of damages, suitability of repairs and residual strength capability, which is minimum Design Limit Load (DLL).
Keywords: Structures & Materials